DİJİTAL GÖRÜNTÜ İŞLEME YÖNTEMLERİYLE LİFLİ BETON NUMUNELERİNDEKİ ÇATLAKLARIN TESPİT EDİLMESİ - ONAT, MAHİR (Fırat Üniveristesi, 2008)
Bu çalışma da, betonun kırılmadan önceki potansiyel davranışının görüntü işleme teknikleri kullanılarak (matlab programında hazırlanan yazılımla) incelenmesi amaçlanmıştır. Bu amaçla 50x10x10 cm. boyutunda dikdörtgen prizma şeklinde lifli beton numuneleri hazırlanmıştır. Ardından bu beton numunelerinin 28 günlük kürü elde edildikten sonra üç noktalı eğilme deneyine tabi tutulmuştur. Yüke karşılık gelen deplasman miktarları bir komparatör yardımıyla ölçülmüştür. Ayrıca deneye tabi tutulan numuneler yüksek çözünürlüklü 10.3 MP CMOS dijital kamerası ile seri çekim yapılarak görüntüleri elde edilmiştir. Bu görüntüler Matlab programında kodlanan yazılımla işlenmiş ve ortaya çıkan deplasman miktarları aynı anda elde edilen komparatör değerleri ile karşılaştırılmıştır.

The purpose of this study is to examine the unbroken concrete potential treatment as use the image processing techniques that prepared in Matlab software. For this purpose, a concrete rectangular prism sample (dimensions 50x10x10 cm.) which contains fiber had prepared. After 28 days old cure had produced from this concrete sample, 3 dotted incline test made on the concrete sample. In this test, the measure of displacement correspond to the load quantity had measured with a comparator, consequently the real values had obtained. The measure of displacement on the sample had viewed with a big dimensional 10.3 active mega pixel CMOS digital photograph machine by serial taking also. These views had processed with a programmed which made in Matlab software. Concurrently, the displacement had compared with the values obtained from comparator values.
Determination of cracks in the fiber concrete sample by using the digital image processing
Keywords: İnşaat Mühendisliği